1995
DOI: 10.1002/app.1995.070581012
|View full text |Cite
|
Sign up to set email alerts
|

In vitro monocyte adhesion and activation on modified FEP copolymer surfaces

Abstract: SYNOPSISThe functional group content and the ionic state of functional groups present on a series of surface modified poly(tetrafluoroethylene/hexafluoropropylene) (FEP) copolymers were characterized by electron spectroscopy for chemical analysis (ESCA), contact angle, and attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR). Additionally, after a protein was preadsorbed on these surfaces, in uitro cell (monocyte) adhesion and activation were analyzed. The two proteins in this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In the present study, we examined the attachment of Chinese hamster ovary (CHO) cells. The kinetics of cell attachment was followed using a Sysmex CDA 500 particle counter, a very simplistic but accurate cell counting method which has been sparingly used. ,, Other methods, which include radioactive labeling, , counting by using a haemocytometer, image analysis, and manual counting 4,14 techniques are more labor intensive, which results in less data being available and larger statistical variation. Data for previous attachment assays has shown large scatter …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we examined the attachment of Chinese hamster ovary (CHO) cells. The kinetics of cell attachment was followed using a Sysmex CDA 500 particle counter, a very simplistic but accurate cell counting method which has been sparingly used. ,, Other methods, which include radioactive labeling, , counting by using a haemocytometer, image analysis, and manual counting 4,14 techniques are more labor intensive, which results in less data being available and larger statistical variation. Data for previous attachment assays has shown large scatter …”
Section: Methodsmentioning
confidence: 99%
“…It has been observed that the specific surface chemistry and polar free energy of polymer substrates can influence the adhesion and subsequent cell growth process, either directly or indirectly through the serum protein layer which rapidly adsorbs onto the surface prior to cell adhesion. Consequently, surface modification treatments such as plasma 3,4,6,[10][11][12] or corona oxidation, 13,14 together with the adsorption of proteins and surfactants, 1,2,5,[15][16][17] have been investigated and shown to positively influence the characteristics of the cell growth process. However, detailed or quantitative studies that establish the relationship between the precise physicochemical properties of the culture system and the response of cells in culture have, until now, been lacking from the literature.…”
Section: Introductionmentioning
confidence: 99%